Kemampuan Kuangan Daerah Studi Kasus Kota Jambi dalam Pelaksanaan Otonomi Daerah - Anita Wulandari (Magister Ilmu Administrasi Publik, 2001)
One of the crucial benchmark for the success of of decentralisation policy in Indonesia is whether it will improve local financial capacity. It is undeniable that, with the centralistic tendency of national development strategy in the past, local governments had been increasingly dependent on the financial resources provided by the central government. With a radical decentralisation policy has been brought into effect in early 2001, it is assumed that local governments will be able to carry out their development responsibilities with the local financial resources. However, it turned out that the policy are hampered by lack of human resources, infrastructure limitations, and rampant corruption among the local authorities. The financial autonomy in this study is measured by the degree of fiscal decentralisation, the fiscal needs, capacity and efforts, the actual local revenue (PAD) and the elasticity of PAD. The case study in the city of Jambi shows that financial autonomy after decentralisation policy is still low. This is caused by some pitfalls in local finance, namely: I) limited potentials for local taxes and levies, 2) increasing misuse of funds in local administration, and 3) inadequate revenues from the local enterprises. To strengthen financial capacity of Jambi city administration, it is recommended to develop an industrial zone and to boost cooperative networks with domestic as well as foreign investors.